2022
DOI: 10.3390/electrochem3030029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Corrosion Inhibition Efficacy of Alkaloid Extract of Artemesia vulgaris and Solanum tuberosum in Mild Steel Samples in 1 M Sulphuric Acid

Abstract: Two different types of alkaloids are successfully extracted from two plants Artemisia vulgaris (AV) and Solanum tuberosum (ST) in the laboratory and used as corrosion inhibitors for mild steel samples. The corrosion inhibition potential of these alkaloids is determined by weight loss and potentiodynamic polarization measurement methods. Based on the weight loss measurement study of a sample immersed for 6 h in 1000 ppm inhibitor solution of AV and ST alkaloids, the corrosion inhibition efficiency is found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…It can be observed that the temperature produced an increase in V corr , even in the presence of PILs, which was attributed to desorption phenomena of the inhibiting macromolecules. In addition, it is shown that the lowest V corr values were obtained at C INH of 175 ppm, indicating that a higher amount of PIL macromolecules can form a more homogeneous protecting film that reduces the diffusion of sulfate ions toward the metallic surface [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the temperature produced an increase in V corr , even in the presence of PILs, which was attributed to desorption phenomena of the inhibiting macromolecules. In addition, it is shown that the lowest V corr values were obtained at C INH of 175 ppm, indicating that a higher amount of PIL macromolecules can form a more homogeneous protecting film that reduces the diffusion of sulfate ions toward the metallic surface [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The poly(SA-Tol-BZ) coating, with its crosslinked network, demonstrated superior corrosion resistance ability compared to bare MS. According to Table S1 , our poly(SA-Tol-BZ) has the highest inhibition effect among other inhibitors in the same corrosive medium [ [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ], suggesting that it is highly effective in inhibiting corrosion and holds great promise for anti-corrosive applications.
Fig.
…”
Section: Methods For Electrochemistrymentioning
confidence: 99%
“…To study the effect of immersion time, the effect of inhibitor's concentration and adsorption isotherm MS specimens were exposed to a corrosive and inhibitor media for a certain time, and subsequent measurements were carried out. Mathematically, the inhibition efficiency and fraction of the surface covered by alkaloids were estimated as per Equations ( 1) and ( 2) [21].…”
Section: Weight Loss Measurement Methodsmentioning
confidence: 99%
“…Tafel slope, corrosion potential, and corrosion current were computed using the polarization curves. Using the formula in Equation ( 3), the corrosion inhibition efficiency was computed [21]:…”
Section: Electrochemical Measurementmentioning
confidence: 99%